MPs between territories, assembly and party – Investigating parliamentary behaviour at the local level in France, Belgium and Germany. Issue 4 (December 2016) - Brack, Nathalie; Costa, Olivier; Kerrouche, Eric
Abstract This article introduces the special issue on constituency representation in France, Belgium and Germany. First, it proposes a brief state of the art to show that the literature on European parliamentary systems concentrates on the legislators' activities in the house but it remains comparatively limited regarding their activities outside Parliament. It is even more so in the three countries under study. This lack of comprehensive knowledge is problematic, considering the centrality of political representation in modern democracies but the current context of declining trust and confidence in representative institutions. Second, it describes the data from the CITREP and IMPLOC(BEL) projects as well as the original methodology used by the articles. Indeed, this special issue takes a new approach and combines different types of data and methods to analyse the concrete practices of parliamentarians on the ground. Finally, this article explains the main research questions, hypothesis and variables to be tested in the special issue, including institutional and individual factors.